E-business challenges in the field of payment solutions - Bitcoin a sustainable currency or gambling - Jacek Binda (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2018)
Money is a widely accepted commodity allowing to determine the economic value of purchased goods and services and to make payments. Over the centuries, "money" has been constantly evolving. In recent times, following dynamic development of various forms of e-business, dematerialized money has emerged. However, in constantly changing conditions it is very difficult to grasp the essence of the so called e-money or cryptocurrencies. The paper tries to define Bitcoin, one of the most recognizable cryptocurrencies, and answer the question whether investing in cryptocurrencies is a serious business or a mere gambling. In search for the answers, the author reviews literature on the topic and conducts his own risk analysis based on Value at Risk measure, of selected traditional currencies and Bitcoin. The results of the analysis unambiguously show that investments in Bitcoin are burdened with definitely much higher risk. Furthermore, conclusions of the considerations clearly show that despite growing popularity of cryptocurrencies they do not fulfill the definition of both electronic money or money in general. The paper attempts to discuss selected issues related to Bitcoin cryptocurrencies from the monetary point of view but also with respect to restrictions of Bitcoin as a means of payment, investments in Bitcoin and risk assessment.